Complex or Simplistic approach (as per Richards Nisbett) by analyzing the culture orientation on media articles - the view of students of Intercultural Management in DOBA Faculty. Case Study - Miše, Mia (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Different cultures perceive events from different point of view. Western cultures deal with the actor or who while Eastern cultures deal with context or why. As Nisbett states in the book “The Geography of Thought” media show the difference in approach and can tell us a lot about the culture of society. In the school year 2016/2017 students of International Week on DOBA Faculty were providing their analyses of their media as per culture analyses based on Nisbett book. We can get some insights about the countries cultures, reflected in national media and as well about the way how students of Summer School on Doba Faculty contemplate and understand the present situation in the world. Interesting answers from their Assignment 2 were gathered and presented shortly for purpose of this article.
Keywords: East values; West values; media approach; interpretation of an event; who versus why; Intercultural Management; Doba Faculty